A Proposed Model of Digital Forensic on Cloud Computing Security Infrastructure - Savitri, Sekar Ayu; Hersyah, Mohammad Hafiz (School of Industrial and System Engineering, Telkom University, 2018)
Over the past decades, practitioners and researchers have made remarkable achievements in digital forensic. The abilities to conquer major technical obstacles are bestowing practitioners greater access to digital evidence. Sophisticated forensic techniques and tools are being developed to assist forensic acquisition and extraction of volatile data, inspection of remote repositories system and analysis of network traffic. Computer forensic is a comprehensive work that based on several attributes that are : objectivity, relevance and legitimacy to compose a system model that projected to be an electronic evidence forensic system. Latest studies show that the rapid growing of cloud computing facilities usage that has enable various improvements as part of the innovation process at organisations. Information systems are in frequently exposed to various types of threats which able to trigger different types of bad consequences as more and more information stored, problems arise especially about security information technology risk aspects. Keywords—computer forensic, cloud computing, electronic evidence forensic system, security, information technology risk, information system